1982
DOI: 10.1097/00006254-198206000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pregnancy in Sickle Cell Anemia

Abstract: There has been significant decrease in maternal morbidity and mortality of sickle cell disease patients during pregnancy due to better understanding of the pathophysiology of the disease and physiologic changes during pregnancy.Prophylactic blood transfusion does not appear to reduce complications in patients with sickle cell anemia. Patients with sickle hemoglobin C disease and with Sp thalassemia' have fewer complications but still need close monitoring.Blood transfusion therapy should be made available for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 2 publications
0
15
1
Order By: Relevance
“…19,28 Seven studies specified outcomes based on b-globin genotype. 10,15,18,19,26,28,30 Confounding variables were generally not addressed in the study design or analysis.…”
Section: Description Of Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…19,28 Seven studies specified outcomes based on b-globin genotype. 10,15,18,19,26,28,30 Confounding variables were generally not addressed in the study design or analysis.…”
Section: Description Of Study Characteristicsmentioning
confidence: 99%
“…Protocols varied across reports and the type of transfusion depended on the degree of anemia in 5 studies. 10,15,16,19,30 Timing of prophylactic transfusion differed, with only 2 studies instituting the intervention in early to midpregnancy. 10,15 The proportion of patients receiving prophylactic transfusion and needing additional on-demand transfusions was not reported in the majority of studies and varied widely in the studies in which it was reported (5.6-60.7%).…”
Section: Summary Of Management and Transfusion Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Affected women are associated with high rates of prenatal and natal complications, and cesarean birth rates tend to be higher in women with SCA (2)(3)(4)(5)(6). Because fetomaternal morbidity and mortality increases with prolonged labor, choosing the right type of delivery is important.…”
Section: Introductionmentioning
confidence: 99%